2018
DOI: 10.1002/gj.3115
|View full text |Cite
|
Sign up to set email alerts
|

Landscape ecological risk assessment in Qinling Mountain

Abstract: In this paper, landscape ecological risk in Qinling Mountain was studied. Using the remote sensing images of Landsat TM and DEM data in 1984, 2000, 2005, and 2014, an ecological risk assessment model was constructed, and landscape ecological risk indexes were calculated for four time periods 1984, 2004, 2005 and 2014. The spatial distribution of ecological risk was obtained with ArcGIS and geostatistics, and changes in the landscape patterns and spatiotemporal characteristics of ecological risk were analysed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 14 publications
0
42
0
Order By: Relevance
“…The landscape disturbance index was calculated by landscape metrics. The landscape fragility index was usually obtained by artificial assignment or the normalization method, while some studies calculated it by using the index, which could quantitatively describe the ecological characteristics of the risk receptor, such as vegetation index, wetness index and topographic index [18]. Either way, both the selection of the assessment method and the construction of ecological risk index should be in accordance with the research purpose and the ecological characteristics of the research object.…”
mentioning
confidence: 99%
“…The landscape disturbance index was calculated by landscape metrics. The landscape fragility index was usually obtained by artificial assignment or the normalization method, while some studies calculated it by using the index, which could quantitatively describe the ecological characteristics of the risk receptor, such as vegetation index, wetness index and topographic index [18]. Either way, both the selection of the assessment method and the construction of ecological risk index should be in accordance with the research purpose and the ecological characteristics of the research object.…”
mentioning
confidence: 99%
“…A study by Yin, Yang, Wang, Liu, and Meng () evaluated the potential land for biofuel plant development in Shaanxi Province, China. In the paper by Cui et al (), landscape ecological risk assessment was undertaken in Qinling Mountain using Landsat remote sensing data. Han, Zhao, Wu, Zhang, et al () used SPOT 6 imagery to extract lithological information in a heavily Quaternary‐covered region of North China.…”
Section: Volume 2: Structure and Main Themesmentioning
confidence: 99%
“…To summarize, agricultural occupation and urban expansion were verified as the two main causes of ecological land loss, as well as elevated risks. In light of the current situation, measures such as policy adjustment and ecological restoration should be taken to avoid risk and optimize land use.Previous studies have measured regional ecological security and detected its influencing factors in view of multi-scale and multi-source data [13][14][15]. Jackson et al evaluated the ecological vulnerability caused by land use changes and economic development in the U.S. Mid-Atlantic region by overlaying the maps of land-use change projections and sensitive ecological resources [16].…”
mentioning
confidence: 99%
“…With the increasing complexity of external environmental factors and the multiple scales of evaluation, more environmental stresses were taken into account, such as urbanization, climate change, and land use change [35]. Studies have demonstrated that a decrease in landscape integrity and stability can lead to a high ecological risk in regional landscapes [14]. Calculating landscape ecological risk and putting forward reasonable risk avoidance measures has been a useful way to improve landscape quality [36].…”
mentioning
confidence: 99%
See 1 more Smart Citation